Green Transformation of Hospitals Evaluation According to Sustainability Criteria: The Case of Afyonkarahisar - Kozan, Fatmanur; Onay, Büşra (European Journal of Applied Sciences, 2024)
This study aimed to determine whether the existing situation of the hospitals in the Afyonkarahisar (Afyon) Provincial center have the green hospital criteria, by emphasizing the importance of green hospitals. In the study, the green hospital suitability evaluation form, which was constituted according to the information obtained from the literature, was filled by the responsible persons by engaging in interviews at the hospitals that were the subject of the study. This form is composed of six headings: sustainable lands, water productivity, energy and atmosphere, materials and sources, quality of interior space, and waste management. The data obtained from each hospital were analyzed with percentage values. The data obtained from the green hospital suitability evaluation forms conducted at hospitals were analyzed and in general they received 73.34% points for sustainable lands, 58.33% for water productivity, 80% for energy and atmosphere, 100% for materials and sources, 80.94% for quality of interior space, and 100% points for waste management. According to the analysis results, it was observed that the hospitals that tried to fit the subject did not fulfill the criteria of being a green hospital in some areas. Suggestions were presented for becoming a green hospital, especially for the hospitals.